Analisis Kebutuhan Fasilitas Ruang Jenazah Untuk Pelayanan Bandara Sultan Hasanuddin - Muhamad Fachri; Ubaedillah Ubaedillah; Lina Rosmayanti (MANAJEMEN, 2025)
Handling of human remains by air transport requires adequate facilities and procedures in accordance with national and international regulations. This study aims to analyze the need for special corpse facilities at Sultan Hasanuddin International Airport Makassar to improve service quality. The research method uses a qualitative approach with data collection techniques such as  observation, interviews, and documentation. The results show that the existing corpse handling facility does not meet service standards, where remains are still handled in the general cargo area without dedicated rooms, cooling systems, or family waiting areas. Development of special corpse facilities is required, including dedicated rooms, refrigeration, ceremonial areas, and family waiting rooms. This development is expected to improve operational efficiency and provide proper respect to the deceased and their families.